Pengaruh Model Flipped Mastery Classroom Berbantuan Flipbook Digital Terhadap Hasil Belajar Ekonomi Siswa SMAN 1 Karanganyar - Elsa Nur Azizah; Leny Noviani; Khresna Bayu Sangka (Jurnal Pendidikan Ekonomi (JUPE), 2022)
This research aims to identify the effect and the magnitude of the effectiveness degree of flipped mastery classroom learning model with flipbook digital aid to economy study results in SMAN 1 Karanganyar. This research is a descriptive quantitative in the form of quasi-experimental with the students of class XI IPS 2 and class XI IPS 4 of SMAN 1 Karanganyar with 60 students in total as the research subject. This research sampling used a purposive sampling technique. Meanwhile, for this research, the data is collected by using tests and observation. The data analysis technique used in this study was the independent sample t-test and normalized gain. This study found that (1) flipped mastery classroom model implementation using flipbook digital aid has a positive effect in improving their economics study result. (2) The effectiveness of flipped mastery classroom learning models assisted by digital flipbooks in improving economic learning outcomes class XI IPS students of SMAN 1 Karanganyar